Qanun and House of Worship Conflict: The Irony of the Aceh Government in Aceh Singkil - ., Muzakkir; ., M. Anzaikhan (Journal of Ecohumanism, 2024)
Resolving the conflict over the legality of the establishment of non-Muslim houses of worship in Aceh Singkil is not an easy matter, especially after the burning of 1 church and the demolition of 9 churches in 2015. The existence of Christian congregations that continue to grow is a ’time bomb’ in the future, considering that not a single church has received its license to date. This research aims to place the ’real’ phenomenon (the latest motive) behind the non-approval of permits for the establishment of non-Muslim houses of worship in Aceh Singkil. This research is an output of the Research Organization for Science and Social Humanities (OR IPSH) Program House of the National Research and Innovation Agency (BRIN) in collaboration with PTKIN Aceh Lecturers. This research is classified as field research with a qualitative approach. The methodology used is a phenomenological study and ethnographic study. Data collection was done through interviews and Qanun observations. The study found that church burning is not a religious conflict but a conflict of political interests. Politicians deliberately maintain religious conflicts (always exist) to obtain majority votes. Second, the motive for not issuing permits for the establishment of non-Muslim houses of worship is a hypocritically packaged ’hands-off policy’. Through Qanun’s affirmation, the executive does not want legality to be issued when they take office.